Titanium oxide films deposited by e‐beam evaporation as n‐type electrode for solar cell applications. Issue 10 (3rd November 2016) - Chierchia, Rosa; Menchini, Francesca; Serenelli, Luca; Mangiapane, Pietro; Polichetti, Tiziana; Tucci, Mario
Abstract: TiO2 is a n‐type oxide semiconductor used in many fields of chemistry and engineering, included dye sensitized and organic solar cells. Different methods have been investigated to prepare TiO2 films, nevertheless its poor electrical and optical characteristics hampers its use as a transparent conductor oxide. In this work thin TiO2 film obtained by e‐beam evaporation and thermally annealed at different temperatures were studied using different characterization techniques, in order to evaluate its use as emitter layer or back contact in silicon based heterojunction solar cells. By Raman analysis we found the TiO2 films showed mainly the presence of anatase crystal structure once thermally annealed at T > 400 °C. Electrical and optical characterization of the thermally annealed samples showed that the best results consisted in a resistivity of around 10 ‐2 Ωcm, a mobility of 3 cm 2 /Vs and carrier concentration of 10 19 /cm 3 . From capacitance‐voltage characteristics of TiO2 /p‐c‐Si, the built‐in potential has been evaluated in order to assess the band alignment with crystalline silicon. Good quality titanium oxide films by using e‐beam evaporation deposition technique followed by thermal annealing have been obtained with physical and electrical properties desirable for photovoltaic applications. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)